EFEK STIMULASI INTERFERENSIAL PADA PENERAPAN LATIHAN SEPEDA STATIS TERHADAP PERUBAHAN NYERI DAN GERAK SENDI LUTUT PASIEN OSTEOARTHRITIS (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2020)
Objective: To determine the effect of interferential stimulation on the application of exercise with a static bicycle to changes in the actuality of pain and range of motion in the knee joints of osteoarthritis patients. Method: This study was a quasi-experimental design with pre and posttest two-group design, where changes in pain actuality and range of joint motion were measured using visual analogue scales and goniometers. A sample of 24 osteoarthritis patients who met the inclusion requirements was divided into two groups: the first group (n = 12) were given static bicycle training and the second group (n = 12) were given static bicycle training and interference stimulation. Results: Based on the statistical analysis of paired sample t-tests there were significant differences in both groups both the actuality of pain and the scope of joint motion before and after the intervention with a value of p = 0,000 in both groups. Statistical analysis with independent sample t-test showed an insignificant difference in the actuality of pain between groups with a value of p = 0.943 and there were significant differences in the scope of joint motion between groups with a value of p = 0.014. Conclusion: There is no significant difference in the effect of the addition of interferential stimulation on static bicycle training on the decrease in pain actuality, but there is a significant difference in the scope of joint motion in osteoarthritis patients.Keywords: Exercise, static bicycle, interference stimulation, osteoarthritis